Reformulasi Pendidikan Agama Bagi Anak-Anak Jalanan: Reformulating Religious Education for Street Children - Soebahar, Abd. Halim (Fenomena, 2002)
The growing number of street children in urban centres such as Jember poses a critical challenge to the effectiveness of religious education, which often fails to address their unique socio-economic realities. This study addresses the gap between conventional religious pedagogy and the lived experiences of marginalised youth by examining five key dimensions: their characteristics, religious knowledge, religious values, religious behaviour, and desired educational patterns. A qualitative approach was employed, involving life-history interviews, non-participant observation, and focus group discussions with 25 purposively selected street children from several locations in Kota Jember. The findings reveal that street children have developed a distinct and exclusive life philosophy, often ambivalent towards formal religious norms. Their religious knowledge remains limited and homogeneous, primarily derived from parents and schools, while peer influence leads to shifts in values and behaviours that mimic a "Si Boy" archetype—simultaneously pious and transgressive. Despite recognising the importance of religious education, they perceive educators as unfriendly and judgemental. The study concludes that a reformulation and revitalisation of religious education is urgently needed, grounded in empathy and an understanding of street children’s evolving paradigms, with recommendations for educators to adopt a more inclusive and context-sensitive approach. Meningkatnya jumlah anak jalanan di pusat-pusat perkotaan seperti Jember menghadirkan tantangan krusial bagi efektivitas pendidikan agama yang sering gagal menjangkau realitas sosial-ekonomi unik mereka. Penelitian ini menjawab kesenjangan antara pendekatan pedagogi agama konvensional dan pengalaman hidup anak marginal dengan mengkaji lima aspek utama: karakteristik, pengetahuan agama, nilai agama, perilaku beragama, dan pola pendidikan yang mereka harapkan. Metode kualitatif digunakan melalui wawancara riwayat hidup, observasi non-partisipan, dan diskusi kelompok terarah terhadap 25 anak jalanan yang dipilih secara purposif dari sejumlah lokasi di Kota Jember. Temuan menunjukkan bahwa anak jalanan mengembangkan filosofi hidup khas dan eksklusif yang ambivalen terhadap norma agama formal. Pengetahuan agama mereka terbatas dan homogen, berasal dari orang tua dan sekolah, sementara pengaruh teman sebaya memicu pergeseran nilai dan perilaku ala “Si Boy”—rajin beribadah sekaligus melakukan pelanggaran. Meskipun menyadari pentingnya pendidikan agama, mereka mempersepsikan pendidik sebagai pihak yang tidak ramah dan menghakimi. Penelitian ini menyimpulkan perlunya reformulasi dan revitalisasi pendidikan agama yang dilandasi empati serta pemahaman terhadap paradigma hidup anak jalanan, dengan rekomendasi agar pendidik mengadopsi pendekatan yang lebih inklusif dan peka konteks.